Optimasi Pemilihan Destinasi Wisata Prioritas Menggunakan Metode ROC dan Weighted Product - Mardianto; Muhallim, Muhlis (Journal Research on Computing Knowledge, 2025)
The choice of suitable tourist locations is a key element in improving the competitiveness of regional tourism. Nonetheless, unstructured and subjective selection methodologies may result in inefficiencies in the planning and development of tourism regions. This research seeks to enhance the selection of priority tourism locations with a Decision Support System (DSS) employing the Weighted Product (WP) method and criteria weighting via the Rank Order Centroid (ROC). Five factors were employed in the assessment: destination distinctiveness, accessibility, supporting infrastructure, economic viability, and media prominence. Each alternative destination was evaluated on a scale of 1 to 5 and subsequently analyzed using the WP method to derive preference scores. The findings indicated that Destination A received the highest preference score of 0.232, so it is suggested as the principal site for development. This method is effective in aiding policymakers in formulating objective, systematic, and data-driven alternative choices